Generation of photoionized plasmas in the laboratory: Analogues to astrophysical sources. Issue Volume 15:Issue S350(2019) (April 2019) - White, S.; Irwin, R.; Warwick, R.; Sarri, G.; Gribakin, G. F.; Keenan, F. P.; Hill, E.; Rose, S. J.; Ferland, G. J.; Wang, F.; Zhao, G.; Han, B.; et al.
Abstract: Implementation of a novel experimental approach using a bright source of narrowband x-ray emission has enabled the production of a photoionized argon plasma of relevance to astrophysical modelling codes such as Cloudy. We present results showing that the photoionization parameter ζ = 4 πF/ne generated using the VULCAN laser was ≈ 50 erg cm s −1, higher than those obtained previously with more powerful facilities. Comparison of our argon emission-line spectra in the 4.15 - 4.25 Å range at varying initial gas pressures with predictions from the Cloudy code and a simple time-dependent code are also presented. Finally we briefly discuss how this proof-of-principle experiment may be scaled to larger facilities such as ORION to produce the closest laboratory analogue to a photoionized plasma.